Biotransformation of fluorene by the fungus Cunninghamella elegans. - Pothuluri, J V (1993)
The metabolism of fluorene, a tricyclic aromatic hydrocarbon, by Cunninghamella elegans ATCC 36112 was investigated. Approximately 69% of the [9-14C]fluorene added to cultures was metabolized within 120 h. The major ethyl acetate-soluble metabolites were 9-fluorenone (62%), 9-fluorenol, and 2-hydroxy-9-fluorenone (together, 7.0%). Similarly to bacteria, C. elegans oxidized fluorene at the C-9 position of the five-member ring to form an alcohol and the corresponding ketone. In addition, C. elegans produced the novel metabolite 2-hydroxy-9-fluorenone.